The effects of customized learn-to-swim programs on water competency in adults ages 20 to 30 years old - Garcia, Mary Mundrieth F. 1999-
Swimming is an essential life skill that promotes physical activity and safety in and around water. While many learn-to-swim programs exist, there is limited research on the impact of customized programs tailored specifically to adults between the ages of 20 and 30 years old. Most learn-to-swim programs are traditional swimming lessons which focus on mostly stroke technique, but are missing out on the importance of water competency and safety (Water Safety USA, 2022). However, this new customized program to be studied will not only be teaching both swimming skills and survival skills, but will use the learning style of the participant using a personalized learning approach. This study aims to investigate the effects of such customized learn-to-swim programs on adults’ swimming abilities and water safety knowledge